Fungal communities differentially respond to warming and drought in tropical grassland soil. Issue 8 (28th April 2020) - de Oliveira, Tássio Brito; de Lucas, Rosymar Coutinho; Scarcella, Ana Silvia de Almeida; Contato, Alex Graça; Pasin, Thiago Machado; Martinez, Carlos Alberto; Polizeli, Maria de Lourdes Teixeira de Moraes
Abstract: Climate change is predicted to cause more extreme events, such as heatwaves, and different precipitation patterns. The effects of warming and short‐term drought on soil microbial communities, in particular fungal communities, remain largely unexplored under field conditions. Here, we evaluated how the fungal community of a tropical grassland soil responds to these changes. A field experiment was carried out in a temperature free‐air controlled enhancement (T‐FACE) facility in Ribeirão Preto, Brazil. The isolated and combined effects of drought and a 2°C increase in temperature were investigated. Based on metabarcoding of the ITS2 region, a total of 771 operational taxonomic units were observed. While warming affected the community structure, drought affected the alpha diversity, and the interaction between warming and drought affected both diversity and structure. The change in community composition driven by warming affected only the less abundant species (>1% of the total sequences). The aspect of the fungal communities that was most affected was diversity, which was increased by drought ( p < .05), mostly by reducing the dominance of a single species, as observed in the watered plots. In a phylogenetic context, some fungal taxa were favoured by changes in temperature (Hypocreales) and drought (Sordariales) or disadvantaged by both (Pleosporales). It was of note that a water deficit increased the abundance of phytopathogenic fungi, such as Curvularia, Thielavia and Fusarium species. Overall, our results provide evidence that fungal communities in tropical grassland soils have greater sensitivity to drought than to temperature, which might increase the incidence of certain soil‐borne diseases.